Mapping the Potential and Challenges of Islamic Economics in Riau Province: A Comparative Study of Districts/Cities Based on the Islamic Economic Index - Sabarno Dwirianto; Martin; Musnawati; Roza Linda; Rendika Adisman (Suria Academic Press, 2026)
Islamic economics has become one of the strategic pillars of regional economic development in Indonesia, including in Riau Province, which holds substantial potential that has not yet been systematically mapped at the district/city level. This study aims to map the potential and challenges of Islamic economic development in Riau Province through a comparative approach across regions based on Islamic Economic Index indicators. The research employs a library research design with a systematic literature review approach and descriptive-qualitative analysis. Data sources consist of official publications from authoritative institutions (BPS Riau Province, Bank Indonesia, KNEKS, OJK, and the Riau Provincial Government) as well as academic literature collected through documentary study techniques and analyzed using content analysis and descriptive-comparative analysis. The results show that Riau holds an institutional advantage as the first province to simultaneously have a Governor Regulation on Islamic Economics, a Regional Committee for Islamic Economy and Finance (KDEKS), and a fully sharia-based regional development bank. The halal industry sector has grown significantly, with halal-certified businesses increasing from 16,050 to 35,432 between 2023 and 2026, accompanied by halal export values reaching US10.43 billion. Riau's financial literacy and inclusion indices were recorded as the highest nationally, although Islamic financial literacy specifically still lags behind. The study also found variation in potential across districts/cities, indicating the need for differentiated policy approaches to Islamic economic development. This research contributes theoretically by enriching subnational Islamic economic mapping studies and practically by serving as a reference for local governments and KDEKS in formulating more contextual and data-driven policies for Islamic economic development in Riau Province.